Guidance on Evaluation Reports - CGIAR Independent Evaluation Arrangement (CGIAR Independent Evaluation Arrangement, 2015)
This Guidance Note includes general guidelines for preparing a CGIAR Evaluation Report and describes the key elements that an Evaluation Report should normally cover.